Optimization of a company’s capital structure based on the criterion of minimizing the level of financial risk - Hanna Filatova; Viktoriya Kulyk; Olena Kravchenko (Accounting and Financial Control)
In the context of growing economic uncertainty, capital structure optimization is becoming a critical tool for minimizing financial risks, providing companies with the necessary stability and adaptability in modern conditions. This paper aims to develop theoretical foundations for the existing capital structure optimization methods and elaborate an optimal capital structure formation strategy to ensure companies’ financial stability and flexibility in conditions of high financial uncertainty. The article offers a stabilization-flexible approach to optimizing companies’ capital structure in financial instability and crises, making it possible to ensure the companies’ financial stability while preserving their ability to adapt to a volatile environment quickly. The main idea of the approach is the balanced use of equity capital and long-term and short-term liabilities to finance various components of assets, which helps to minimize risks and increase the efficiency of financial management. A roadmap for the implementation of the stabilization-flexible approach to optimizing the capital structure has been formed, the basis of which is the construction of a logical chain of actions, including the definition of companies’ goals, the assessment of available financial resources and risks, and the development of financing strategies, their implementation, further control and monitoring of results. The study results can be helpful for financial managers, analysts, and investors seeking to improve the efficiency of capital management and reduce the impact of external and internal risks on the financial condition of companies.